Time-to-Degree for the Economics Ph.D. Class of 2001–2002 - Stock, Wendy A; Siegfried, John J (American Economic Review, 2006)
Survey responses from Ph.D. graduates and thesis advisors are used to estimate the time required for the class of 2001-02 to earn a degree. Median time to earn the Ph.D. is 5.5 years, up from 5.25 years for the class of 1996-97. The time required to write a dissertation is a little longer than the time required to complete comprehensive examinations and coursework. Graduates who had their first child while in a Ph.D. program are estimated to finish almost one year later than others. Those with predominantly fellowship support finished about six months faster than those funded predominantly by a teaching assistantship, as did those whose dissertation was a set of essays rather than a single topic treatise. Americans who did their undergraduate work at either a Top-50 U.S. liberal arts or other U.S. college or university that does not offer a Ph.D. in economics finished faster than their counterparts who earned a bachelor’s degree from a U.S. university that offers a Ph.D. in economics. International students from predominantly English speaking countries finished faster than other students studying in the U.S. on temporary visas.